1988
DOI: 10.1677/joe.0.1190031
|View full text |Cite
|
Sign up to set email alerts
|

The anabolic actions of growth hormone and thyroxine on protein metabolism in Snell dwarf and normal mice

Abstract: The individual effects of GH and thyroxine (T4) on protein metabolism were determined in dwarf and normal mice in vivo. The hormone deficiencies of dwarf mice (low serum concentrations of GH and T4) resulted in decreased protein synthesis rates in skeletal muscle and liver, but no difference in synthesis rates in heart. The efficiency of synthesis (g protein/g RNA per day; KRNA) was lower in all three tissues in dwarf compared with normal mice, but effects on RNA concentration were not consistent; there was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Contributions of hepatic protein synthesis to hepatic 0 2 consumption are available in the literature for a variety of species (Table 3) and are affected by physiological manipulation. Similarly, the gastrointestinal tract contributes substantially to wholebody 0 2 utilization (Huntington & McBride, 1988), and even though it only amounts to Thyroidectomy decreases the FSR of skeletal muscle in rats (Brown & Millward, 1983) whereas T3 treatment of mice or rats increases rates of protein synthesis (Carter et al 1982;Bates & Holder, 1988;Jepson et al 1988) (see Table 4). The study of Jepson et al (1988) indicated a significant linear relationship between the rate of muscle protein synthesis and T3 treatment.…”
Section: Protein S Y N T H E S I Smentioning
confidence: 99%
“…Contributions of hepatic protein synthesis to hepatic 0 2 consumption are available in the literature for a variety of species (Table 3) and are affected by physiological manipulation. Similarly, the gastrointestinal tract contributes substantially to wholebody 0 2 utilization (Huntington & McBride, 1988), and even though it only amounts to Thyroidectomy decreases the FSR of skeletal muscle in rats (Brown & Millward, 1983) whereas T3 treatment of mice or rats increases rates of protein synthesis (Carter et al 1982;Bates & Holder, 1988;Jepson et al 1988) (see Table 4). The study of Jepson et al (1988) indicated a significant linear relationship between the rate of muscle protein synthesis and T3 treatment.…”
Section: Protein S Y N T H E S I Smentioning
confidence: 99%
“…In 1973, Korner [73] argued that, irrespective of the types of proteins, the increase in the rate of protein synthesis in the liver stimulated by GH is regulated at the cytoplasmic level. GH treatment of Snell dwarfs (also deficient in GH/IGF-I signaling) is associated with an increase in liver growth [74] and rate of protein synthesis [75]. Similar to the reduction of polysomes in long-lived yeast [76] and flies [55], comparisons of polysome profiles in dwarf and normal-size mice also showed a lower proportion of polysomes to monosomes, which are restored to normal with GH, but not with T3, treatment [77].…”
Section: Humansmentioning
confidence: 90%
“…CK delta = 1789.7 -33.1 x (f-testosterone) -482.3 x (fT 4 ) This model indicates that the lower the basal f-testosterone and fT 4 levels in the athletes, the greater the degree of CK elevation in response to the soccer match. This finding suggests that these athletes were experiencing greater degree of muscle damage during the match than those athletes with higher basal f-testosterone and fT 4 levels.…”
mentioning
confidence: 97%
“…The anabolic actions of f-testosterone are well-established. But, fT 4 also has such anabolic actions by both direct and indirect means; that is, via the conversion of T 4 to T 3 and this hormone's subsequent anabolic effects (4,5). Interestingly, the latter hormone (fT 3 ) nearly reached significance to enter the regression model.…”
mentioning
confidence: 99%
See 1 more Smart Citation